Optimizing Central Pattern Generators (CPG) Controller For One Legged Hopping Robot By Using Genetic Algorithm (GA) - Chong, Shin Horng; Azahar, Arman Hadi; Mohamed Kassim, Anuar; Zainal Abidin, Amar Faiz; Harun, Mohamad Haniff; Nor Shah, Mohd Badril; Mohd Annuar, Khalil Azha; Manap, Mustafa; Rizman, Zairi Ismael (Science Publishing Corporation, 2018)
This paper presents the optimization process of Central Pattern Generator (CPG) controller for one legged hopping robot by using Genetic Algorithm (GA).To control the one legged hopping robot,a CPG controller is designed and integrated with a conventional ProportionalIntegral (PI) controller.Conventionally,the CPG parameters are tuned manually.But by using this method,the parameters produced are not exactly the optimum parameters for the CPG. Therefore,a computational stochastic optimization method; GA is designed to optimize the CPG controller parameters. The GA is designed based on minimizing the error produced towards achieving the reference height.The re-sponse of the one legged hopping robot is compared and the results of the error towards reference height are analyzed.